ANALISIS TINGKAT PENGANGGURAN TERBUKA DI MASA PANDEMI COVID-19 DI INDONESIA - Riza Fahlapi; Endang Susanto, Aulya Indah Sari, Ayi Suryani, Pina Sintia, Seli Indah Lestari (ADISAM PUBLISHER, 2024)
This study aims to analyze determine the effect of various government efforts on reducing the level of open employment in Indonesia at 2021. The approach to this study uses quantitative descriptive analyze. The analysis technique used is using a one-sample t-test (t-test) with hypotesis that there is no a significat increase in open unemployment in Indonesia at 2021 and 2020. The results of this study show that there is an increase at the open unemployment rate in Indonesia at 2021 by 0.31%